PERANAN KELOMPOK TANI DAN PENDAPATAN PETANI UBI KAYU DI DESA SISWO BANGUN KECAMATAN SEPUTIH BANYAK KABUPATEN LAMPUNG TENGAH - Haryadi Haryadi; Indah Nurmayasari; Begem Viantimala (Lampung University, 2019)
The purposes of this study are to examine the role of cassava farmer groups, factors related to the role, the level of cassava farming income and the relationship between the role and the income in Siswo Bangun Village, Seputih Banyak District, Central Lampung Regency. Respondents were 87 cassava farmers involved in 18 farmer groups. This research was conducted in January 2018 and used a survey method. Data analysis used descriptive analysis and Rank Spearman correlation test. The results showed that the level of the role of farmer groups was classified as moderate. Factors significantly related to the role of cassava farmer groups were the role of extension workers and leadership of farmer group leaders. Cassava farming income in Siswo Bangun Village, Seputih Banyak District, Central Lampung regency was classified as moderate, which was Rp21.925.801 per ha per season. There is no significant relationship between the role of farmer groups and the level of cassava farming income Key words: cassava, farming income, role of farmer groups